Iridoids from the aerial parts of Verbena littoralis (Verbenaceae) - Castro-Gamboa, I; Castro, O. (Elsevier B.V., 2004)
The iridoids, 6S-hydroxy-8S-methyl-4-methylene-hexahydro-cyclopenta[c]pyran-3-one and 6S,9S-dihydroxy-8S-methyl-4methylene-hexahydro-cyclopenta[c]pyran-3-one, were isolated from the aerial parts of Verbena littoralis. Their structures and stereochemistry were elucidated by means of NMR spectral data analysis. Both compounds showed moderate in vitro activity against gram positive and negative bacteria as well as moderate in vivo intestinal peristaltic action in mouse. The iridoids also showed moderate free radical scavenging activity against 1,1-diphenyl-2-picrylhydrazyl (DPPH) as well as antioxidant activity, the latter being evidenced by redox properties measured using EICD-HPLC. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Verbena littoralis; Verbenaceae; iridoids; antibacterial activity; antioxidant